HIV/AIDS Knowledge among Secondary School Students in Tanzania: A Case of Misungwi District in Mwanza Region (Tanzania Medical Journal, 2024)
Background Based on the latest UNAIDS report on the global AIDS epidemic; about 34 million people worldwide are estimated to live with HIV and about 69% are found in Sub-Saharan Africa. In Tanzania, people living with HIV/AIDS are estimated to be 1.6 million, of which, 1.3 million belong to the age of 15 years and above. This study aimed to assess the general knowledge on HIV/AIDS among secondary school students in the Misungwi district.MethodsA cross-sectional study design was employed involving 330 students. Information concerning knowledge on causes, risk factors, transmission routes, signs and symptoms as well as preventive measures of HIV/AIDS was collected using a self-assessment structured questionnaire. Data were analyzed using STATA. Mean and standard deviation summarized the numerical variables. Categorical variables were summarized using frequency and proportions. A linear regression model was used to determine the relationships between knowledge score and exposure variables. Multivariable were used to control for confounders. The significance level was set at 5%.ResultsMajority of students had the age of 16 – 18 years old. Males were 64% of the sample. The study found that age, sex and level of classes had influence on the knowledge on symptoms, risk factors and general knowledge about HIV/AIDS. Age appeared to influence HIV symptoms, risk factors and general knowledge (p<0.05). Age was negatively associated with knowledge.ConclusionThe study found that age, sex and school grade influence the general knowledge on HIV/AIDS, its symptoms and risk factors. Therefore, stakeholders should continue providing education on HIV to the youth of all ages and sex.